Multiple Use Water Services To Address Real Life Water Needs - van Koppen, Barbara (2009)
Poor communities in rural and peri-urban areas diversify their livelihoods by farming in backyards and gardens, keeping livestock and processing crops or running micro enterprises such as small restaurant or brick making. Only with an adequate water supply can real life multiple water needs be met most conventional water supply system falls short. Systems are typically designed for a single use only either for domestic use or single productive use such as irrigation. Yet, in reality villagers invariably use these schemes for multiple purposes. Water supply system designed for multiple uses from the outsets, can make a difference to the lives of poor communities by improving food security and income as well as health and wellbeing. In addition to alleviate poverty, multiple use approaches also reduce unpaid workloads and enhance gender equity.